IScore, a useful prognostic tool for patients with acute ischemic stroke treated with intravenous thrombolysis: a validation study - Valéria Cristina Scavasine; Rebeca Teixeira Costa; Viviane de Hiroki Flumignan Zétola; Marcos Christiano Lange (Arquivos de Neuro-Psiquiatria)
Background Stroke is one of the major causes of disability and mortality worldwide. Up to 30% of individuals who experience stroke die within 30 days, and more than 50% of those who survive will have some degree of disability. There are some predetermining factors based on admission data that could be used to objectively assess the odds of poor outcomes, including the Ischemic Stroke Predictive Risk Score (IScore). Objective To analyze and validate the IScore in patients undergoing intravenous thrombolysis for stroke and compare the results of this predictor with actual death and disability outcomes. Methods In a retrospective study, data were collected from a database housed at the Stroke Unit of the Teaching Hospital of Universidade Federal do Paraná, Southern Brazil. The IScore was applied to admission data from 239 patients, and the results were compared with actual outcomes (death and disability) within 30 days and 1 year after the stroke event. Data analysis was performed using an analysis of the receiver operating characteristic (ROC) curve to determine the sensitivity and specificity of the IScore in the study population. Results The IScore demonstrated moderate sensitivity and high specificity in patients with stroke who underwent thrombolysis when evaluated after 30 days and 1 year of the event. Conclusions The IScore can be applied to in stroke patients undergoing thrombolysis; therefore, it may be used as an objective prognostic tool to guide clinical decision-making. Understanding the prognosis of patients in the acute phase can assist clinicians in making the best therapeutic decisions and enable better end-of-life care.